Dampak Covid-19 terhadap Pendapatan Pedagang Pasar Tradisional di Desa Limehe Timur - Hairuddin, Hairuddin; Mardiana, Andi (Madani: Jurnal Pengabdian Ilmiah, 2021)
The article aims to examine the impact of Covid 19 on the income of traditional market traders in East Limehe Village. In the midst of the Covid-19 pandemic outbreak that is happening in the community, especially traders and also since several areas have imposed restrictions on the movement of people, the crowd has done partial quarantine so that many traders are losing money because buyers are very rare or even absent. Before Covid 19, visitors to the market were very busy. However, with the emergence of the Covid 19 pandemic which shocked all regions in Indonesia, especially East Limehe Village, the number of visitors who came has begun to decrease. The reason is because of the social restriction policies and prevention of the spread of Covid 19 imposed by the government. This research was carried out in the implementation of the KKS integrated community service program as an effort to participate in Tabongo District, especially East Limehe Village, so that the community, especially traditional market traders, during this pandemic period. The approach steps used are as follows: Planning, preparation, implementation.